Red flags for appropriate referral to the gastroenterologist and the rheumatologist of patients with inflammatory bowel disease and spondyloarthritis. (9th January 2019) - Felice, C; Leccese, P; Scudeller, L; Lubrano, E; Cantini, F; Castiglione, F; Gionchetti, P; Orlando, A; Salvarani, C; Scarpa, R; Vecchi, M; Olivieri, I; et al.
Summary: Collaboration between gastroenterologists and rheumatologists is recommended for the correct management of patients with associated spondyloarthritis (SpA) and inflammatory bowel disease (IBD). We aimed to establish the appropriateness of several red flags for a prompt specialist referral. A systematic review of the literature was performed using the GRADE method to describe the prevalence of co-existing IBD-SpA and the diagnostic accuracy of red flags proposed by a steering committee. Then, a consensus among expert gastroenterologists and rheumatologists (10 in the steering committee and 13 in the expert panel) was obtained using the RAND method to confirm the appropriateness of each red flag as 'major' (one sufficient for patient referral) or 'minor' (at least three needed for patient referral) criteria for specialist referral. The review of the literature confirmed the high prevalence of co-existing IBD-SpA. Positive and negative predictive values of red flags were not calculated, given the lack of available data. A consensus among gastroenterology and rheumatology specialists was used to confirm the appropriateness of each red flag. Major criteria to refer patients with SpA to the gastroenterologist included: rectal bleeding, chronic abdominal pain, perianal fistula or abscess, chronic diarrhoea and nocturnal symptoms. Major criteria to refer patients with IBD to the rheumatologist included: chronic low back pain, dactylitis, enthesitis and pain/swelling of peripheral joints. Several major and minor red flags have been identified for the diagnosis of co-existing IBD-SpA. The use of red flags in routine clinical practice may avoid diagnostic delay and reduce clinic overload. Graphical Abstract: